2019
DOI: 10.1071/rd17357
|View full text |Cite
|
Sign up to set email alerts
|

Zebularine significantly improves the preimplantation development of ovine somatic cell nuclear transfer embryos

Abstract: Aberrant DNA methylation reduces the developmental competence of mammalian somatic cell nuclear transfer (SCNT) embryos. Thus, hypomethylation-associated drugs are beneficial for improving reprogramming efficiency. Therefore, in the present study we investigated the effect of zebularine, a relatively novel DNA methyltransferase inhibitor, on the developmental potential of ovine SCNT embryos. First, reduced overall DNA methylation patterns and gene-specific DNA methylation levels at the promoter regions of plur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…In most cancer cells, Zb shows a consistent pattern of growth inhibition and demethylation effects with little evidence of toxicity (Cheng et al, ; Cheng et al, ). In embryo production studies, Zb has been applied to modify the epigenetic status of donor fibroblast cells, and it could enhance the subsequent in vitro developmental competence and quality of SCNT embryos of pigs (Diao et al, ), yaks (Xiong et al, ), and sheep (Cao et al, ; Fang et al, ). In the present study, we first investigated the effects of Zb treatment in a porcine IVP system, and we found that supplementation with Zb during IVC could affect the subsequent embryo development of SCNT embryos in different ways according to its concentration and treatment time.…”
Section: Discussionmentioning
confidence: 99%
“…In most cancer cells, Zb shows a consistent pattern of growth inhibition and demethylation effects with little evidence of toxicity (Cheng et al, ; Cheng et al, ). In embryo production studies, Zb has been applied to modify the epigenetic status of donor fibroblast cells, and it could enhance the subsequent in vitro developmental competence and quality of SCNT embryos of pigs (Diao et al, ), yaks (Xiong et al, ), and sheep (Cao et al, ; Fang et al, ). In the present study, we first investigated the effects of Zb treatment in a porcine IVP system, and we found that supplementation with Zb during IVC could affect the subsequent embryo development of SCNT embryos in different ways according to its concentration and treatment time.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, there are two approaches to facilitate reprogramming process of DNA methylation, either on donor cells to decrease the methylation status before SCNT (Cao et al, ; Sun et al, ) or during early cultivation of cloned embryos to mimic the demethylation process as in vivo embryos (Zhai et al, ). Several DNA methyltransferase (DNMT) inhibitors, such as 5‐azacytidine, zebularine and RG108, have been applied to assist somatic nucleus to mimic DNA methylation to an optimal status for further reprogramming process (Cao et al, ; Huangfu et al, ; Zhai et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cluster two in bright green consists of 13 words referring to the development efficiency of cloned embryos at the blastocyst stage using different types of cells as donor of genetic information, most commonly cumulus cells and fibroblasts. The cells were treated with egg extracts [51], zebularine [47], chaetocin [52] and histone demethylase enzymes [53] to promote the nuclear reprogramming of somatic cells and improve the epigenetic status of ovine cloned embryos.…”
Section: Discussionmentioning
confidence: 99%